Neurofilament light chain: A prognostic biomarker in amyotrophic lateral sclerosis. (2nd June 2015) - Lu, Ching-Hua; Macdonald-Wallis, Corrie; Gray, Elizabeth; Pearce, Neil; Petzold, Axel; Norgren, Niklas; Giovannoni, Gavin; Fratta, Pietro; Sidle, Katie; Fish, Mark; Orrell, Richard; Howard, Robin; et al.
Abstract : Objective: To test blood and CSF neurofilament light chain (NfL) levels in relation to disease progression and survival in amyotrophic lateral sclerosis (ALS). Methods: Using an electrochemiluminescence immunoassay, NfL levels were measured in samples from 2 cohorts of patients with sporadic ALS and healthy controls, recruited in London (ALS/control, plasma: n = 103/42) and Oxford (ALS/control, serum: n = 64/36; paired CSF: n = 38/20). NfL levels in patients were measured at regular intervals for up to 3 years. Change in ALS Functional Rating Scale–Revised score was used to assess disease progression. Survival was evaluated using Cox regression and Kaplan–Meier analysis. Results: CSF, serum, and plasma NfL discriminated patients with ALS from healthy controls with high sensitivity (97%, 89%, 90%, respectively) and specificity (95%, 75%, 71%, respectively). CSF NfL was highly correlated with serum levels ( r = 0.78, p < 0.0001). Blood NfL levels were approximately 4 times as high in patients with ALS compared with controls in both cohorts, and maintained a relatively constant expression during follow-up. Blood NfL levels at recruitment were strong, independent predictors of survival. The highest tertile of blood NfL at baseline had a mortality hazard ratio of 3.91 (95% confidence interval 1.98–7.94, p < 0.001). Conclusion: Blood-derived NfL level is an easily accessible biomarker with prognostic value in ALS. The individually relatively stable levels longitudinally offer potential for NfL as a pharmacodynamic biomarker in future therapeutic trials. Classification of evidence: This report provides Class III evidence that the NfL electrochemiluminescence immunoassay accurately distinguishes patients with sporadic ALS from healthy controls.